THE ANALYSIS OF THE RELATIONSHIP BETWEEN MARKETING STRATEGIES AND THE PERFORMANCE OF SMALL AND MEDIUM SIZED BUSINESSES IN ROMANIA - PAȘTIU, Carmen Adina; MUREȘAN, Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
In this current study our aim was to analyze the marketing tactics, namely the strategic planning, market segmentation, correlation between the marketing activities and the firms’ performances, as well. In this context, we intended to examine both the marketing practices and the associations between practices and performance. The marketing policy implies all the main aspects of the processes concerning the supply, dispatch, research-development and supervision of products consumption behavior. Its realization is being done by the marketing strategy.